Simultaneously delivery of functional gallium ions and hydrogen sulfide to endow potentiated treatment efficacy in chemo- and PARPi-resistant ovarian cancer - Sangsang Tang; Yangyang Li; Yifeng Fang; Mengyan Tu; Shenglong Wu; Yixuan Cen; Junfen Xu (Journal of Nanobiotechnology)
Abstract Limited therapeutic options are available for patients with platinum-resistant ovarian cancer (OC). Herein, we developed gallium sulfide-embedded bovine serum albumin nanoformulations (Ga2S3-BSA NMs) with a size of ~ 11 nm via a self-assembly approach. As the nanoformulations degraded in an acidic cancer microenvironment, Ga3+ and H2S gas were simultaneously released to exert their combined anticancer effects. In A2780-CIS and SKOV3-CIS platinum-resistant OC cells, Ga3+ and H2S released from Ga2S3-BSA NMs synergistically enhanced DNA damage, which arrested the cell cycle at S and G2/M phases and suppressed cell proliferation. Meanwhile, Ga2S3-BSA NMs significantly inhibited NF-κB signaling and Bcl2 protein expression, leading to cell apoptosis. Furthermore, Ga2S3-BSA NMs increased cellular lipid peroxidation and triggered ferroptosis. RNA-seq analysis further clarified the comprehensive antitumor mechanisms of Ga2S3-BSA NMs. More importantly, the therapeutic efficacy of Ga2S3-BSA NMs and their ability to enhance the sensitivity to carboplatin and fluzoparib with negligible toxicity were further confirmed in a platinum-resistant OC animal model. Altogether, our results demonstrated a potentially safe and practical strategy by using Ga2S3-BSA NMs to combat drug resistance in platinum-resistant OC. Graphical Abstract